Analysis and Review of The Implementation of Law Enforcement Operations Juridical Capture Corruption in The Criminal Justice System - Hulman Siregar; Rakhmat Bowo Suharto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Corruption has occurred in all sectors of activity in State Institutions has even been categorized as an extraordinary crime. This condition has a negative impact on the implementation of sustainable national development to improve the welfare of the community. Because the state budget funds both central and regional that can be used to build infrastructure facilities for public services such as health services, education, social assistance in the form of food and clothing. Become reduced due to corruption. The mindset and pattern of action in dealing with corruption crime requires a leap of change so that the implementation of law enforcement in combating corruption through hand-catching operations can run effectively in accordance with the laws and regulations.Keywords: Planned; Accurate; Accountable; Responsible.